Aging and decision making: How aging affects decisions under uncertainty - Alec Sproten; Carsten Diener; Christian Fiebach; Christiane Schwieren (University of Heidelberg, Department of Economics, 2010)
In an aging society, it becomes more and more important to understand how aging affects decision making. Older adults have to face many situations that require consequential financial decisions. In the present study, we examined the effects of aging on decisions in two domains of uncertainty: risk and ambiguity. For this purpose, a group of young and older adults played a card game which was composed of risky and ambiguous conditions. In the risk condition, participants knew the probabilities to win or loose the game (i.e. full information), whereas in the ambiguous condition, these probabilities were unknown (thus, there was lack of information). When confronted with risky decisions, the behaviour of older and young adults (measured by the number of times participants chose a gamble instead of a sure amount of money) did not differ. In contrast, under ambiguity, there were significant age-effects in decision making: older people were less ambiguity-averse than young subjects. We conclude that there exist differences in uncertainty-processing between young and older adults, and discuss possible explanations of these differences.
urn:nbn:de:bsz:16-opus-113615
Keywords: J14; C91; 330; Age differences; experiment; risk and uncertainty; Entscheidung unter Unsicherheit; Risikoaversion; Altersgruppe; Test